In-situ laboratory X-ray diffraction applied to assess cement hydration. - De Matos, Paulo R.; Neto, José da Silva Andrade; Jansen, Daniel; Gómez-de-la-Torre, María de los Ángeles; Kirchheim, Ana Paula; Campos, Carlos E. M. (Elsevier, 2022)
In-situ X-ray diffraction (XRD) is a powerful tool to assess the hydration of cementitious materials, providing time-resolved quantitative analysis with reasonable accuracy without disturbing sample. However, the lack of guidelines and well-established procedures for data collection and analysis is the limiting factor for spreading this technique. This paper discussed using in-situ laboratory XRD to assess cement hydration. The first part was dedicated to a literature review on the topic. Then, experimental strategies were discussed, and recommendations related to the data analysis routine were drawn; the advantages and limitations of this technique were also discussed. We can conclude that the critical factors for a successful analysis are the choice of an adequate experimental setup with good statistics and low measurement time, the proper consideration of different amorphous contributions in the XRD pattern, and a good data analysis routine. Independent techniques are highly recommended to support the in-situ XRD data.
Keywords: Hormigón - Microscopía; Rayos X - Difracción; Cemento; In-situ XRD; Laboratory XRD; Cement hydration; Difracción de rayos-X